Transfers, Diversification and Household Risk Strategies : Can productive safety nets help households manage climatic variability? - Macours, Karen (Oxford University Press, 2022)
Despite increasing climatic variability and frequent weather shocks in many developing countries, there is little evidence on effective policies that help poor agricultural households manage risk. This paper presents experimental evidence on a program in rural Nicaragua aimed at improving households’ risk-management through income diversification. The intervention targeted agricultural households exposed to weather shocks and combined a one-year conditional cash transfer with vocational training or a productive investment grant. We identify the relative impact of each complementary package based on randomized assignment and analyse how impacts vary by exposure to exogenous drought shocks. The results show that both complementary interventions provide protection against weather shocks two years after the programme ended. Households that received the productive investment grant also had higher average consumption levels. The complementary interventions facilitated income smoothing and diversification of economic activities, as such offering better protection from shocks compared to beneficiaries of the basic conditional cash transfer and control households. Relaxing capital constraints induced investments in non-agricultural businesses, while relaxing skills constraints increased wage work and migration in response to shocks. These results show that combining safety nets with productive interventions relaxing skill or capital constraints can help households become more resilient and manage climatic variability.